answersLogoWhite

0


Best Answer

8007 to be rigfht

User Avatar

Wiki User

โˆ™ 2009-05-25 17:29:41
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.8
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1984 Reviews

Add your answer:

Earn +20 pts
Q: Simplify 5k plus 7 plus 3k?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you simplify 5k plus 7 plus 3k?

5k + 7 + 3k can be simplified into 8k + 7


What is 5k plus 7 plus 3k?

It is 8k+7 simplified


How do you simplify 4k-10 plus 7-7k?

answer=3k-3


What is 5k 7 3k?

The K stands for thousand. So 5k is 5,000 and 7 3K is either 73,000 or 7,000 and 3,000.


What is the answer to 8k-7-3k 1?

8k-7-3k=1? 5k-7=1 5k=8 k=8/5 8k-7 =-3k+1 11k-7=1 11k=8 k=8/11 8k-7-3k+1=0 5k-6=0 5k=6 k=6/5=1.2 depends on where = sign is in the question


What is the answer to 5k 7 3k?

5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.5k 7 3k is a string of terms: it is not an equation (or inequality) and so cannot have an answer. It is not even an expression since there are no operators between the three terms.


What is the answer to -2k3 plus k2 - 9 from 5k3 - 3k plus 7?

(5k3 - 3k + 7) - (-2k3 + k2 - 9) = 7k3 - k2 - 3k + 16


What is k plus 3k plus 3k equals 49?

It simplifies to 7k = 49 which gives k = 7.


What is the answer to 3k plus 14 equals k?

==> 3k+14=k ==>3k-k=-14 ==>2k=-14 ==>k=-7 ans...


What is the answer when you combine like terms to simplify the expression when it is 4k -10 7-7k?

It is: 4k-10+7-7k combines to -3k-3


How do you simplify 8k plus 2k plus 7?

8k +2k + 7 = 10k + 7


What is the answer to 4k-3 equals 3k plus 4?

Take 3k from both sides to get k-3 equals 4, so k is 7

People also asked